Impact of serum Adiponectin and Leptin levels in acute leukemia - SALAHA AREF; Lamiaa Ebrahim; Emaad Azmy; Rasha AlAshery (Mediterranean Journal of Hematology and Infectious Diseases)
Adipocytokines was stated to exert biological effect on tumor cells. Two adipokines; leptin, and adiponectin in particular, have come to be recognized for their influence on tumor biology including leukemia. The data regarding the prognostic effect of soluble leptin and adiponectin concentrations in acute leukemia patients remains to be identified.